Envy - Levinson, Barry; Weinstein, Paula; Adams, Steve; Stiller, Ben, 1965-; Black, Jack, 1969-; Weisz, Rachel, 1970-; Poehler, Amy, 1971-; Walken, Christopher, 1943-; Maurice-Jones, Tim.; Linder, Stu.; Daily, Blair; Mothersbaugh, Mark; et al. (Universal City, CA : Universal, 2004)
Tim and Nick, best friends, neighbors and co-workers, are suddenly tripped up when one of Nick's harebrained, get-rich-quick schemes actually succeeds. VaPooRizer is a spray that literally makes dog poop, or any other kind of poop for that matter, evaporate into thin air. Tim, who had no faith in Nick's idea, passed on an opportunity to get in on the deal, can only watch as Nick's fortune -- and Tim's own envy -- grow to equally outrageous proportions. When the flames of jealousy are fanned by an oddball drifter who imposes himself into the situation, Tim's life careens wildly out of control.
Director of photography, Tim Maurice Jones ; editors, Stu Linder, Blair Daily ; music Mark Mothersbaugh ; costume designer, Gloria Gresham ; production designer, Victor Kempster.
Ben Stiller, Jack Black, Rachel Weisz, Amy Poehler, Christopher Walken.
MPAA rating: PG-13; for language and sexual/crude humor.
DVD ; Region 1, full screen (1.33:1) presentation and widescreen presentation; Dolby Digital, DTS, SDDS.
Closed-captioned.
Keywords: Envy -- Drama; Male friendship -- Drama; Inventions -- Drama; Animal waste -- Drama; Feature films; Comedy films